Räumliche Verbundsysteme in der agrarischen Produktion - Windhorst, Hans-Wilhelm (ERDKUNDE, 1993)
New forms in the organization of agricultural production developed in western industrialized as well as in Third World countries as a consequence of the industrialization of agriculture. Characteristic of this process is the development of joint production systems which can be found on the micro, meso, and macro level. This paper presents results of recent studies analyzing such production systems. Based on these case studies, the paper tries to answer why similar phenomena can be observed in the formation of such spatial systems in plant and in animal production (convergence). It can be shown that different steering factors become effective on the micro, meso, and macro level. It is noteworthy that similar systems of joint production have developed in agriculture and manufacturing (congruence). Reduction of transportation costs and energy consumption, as well as other factors, are responsible for this convergence. An increasing automation, just-in-time delivery, the formation of multi-enterprise companies, even on a supranational scale, are further phenomena which indicate that a far reaching similarity has developed in the organisation and spatial linkage of joint production systems in the primary and secondary production sectors.